The Role of Vitamin E in Preventing and Treating Osteoarthritis – A Review of the Current Evidence - Chin, Kok-Yong; Ima-Nirwana, Soelaiman (Frontiers in Pharmacology, 2018)
Osteoarthritis is a debilitating disease of the joint involving cartilage degeneration and chondrocytes apoptosis induced by oxidative stress. The current pharmacotherapies emphasize pain and symptomatic management of the patients but do not alter the biological processes underlying the cartilage degeneration. Vitamin E is a potential agent to prevent or treat osteoarthritis due to its antioxidant and anti-inflammatory effects. This review aims to summarize the current evidence on the relationship between vitamin E and osteoarthritis derived from preclinical and human studies. Cellular studies showed that vitamin E mitigated oxidative stress in cartilage explants or chondrocyte culture invoked by mechanical stress or free radicals. Animal studies suggested that vitamin E treatment prevented cartilage degeneration and improve oxidative status in animal models of osteoarthritis. Low circulating or synovial vitamin E was observed in human osteoarthritic patients compared to healthy controls. Observational studies also demonstrated that vitamin E was related to induction or progression of osteoarthritis in the general population. Vitamin E supplementation might improve the outcomes in patients with osteoarthritis, but negative results were also reported. Different isomers of vitamin E might possess distinct anti-osteoarthritic effects. As a conclusion, vitamin E may retard the progression of osteoarthritis by ameliorating oxidative stress and inflammation of the joint. Further studies are warranted to develop vitamin E as an anti-osteoarthritis agent to reduce the global burden of this disease.